Family Functioning Related to Sexual and Reproductive Health in Early Adolescents - Kananit Sanghirun (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Family plays an important role in promoting sexual and reproductive health (SRH) among early adolescents. The purpose of this descriptive qualitative study was to explore family functioning related to SRH in early adolescents. Purposive sampling and snowball techniques were used to recruit 28 biological parents of early adolescents aged 10-13 years from 14 families. Family interviews with both mothers and fathers were conducted using a family interview guide. Data were analyzed using thematic analysis. Findings can be categorized into four categories: 1) parental perceptions of the growing child, including children are not ready to know about sex, having appropriate gender roles, sexual growth and changes in teenagers, and focus on good genital hygiene; 2) parenting practices to promote sexual health, including playfully monitoring teenage friendships, warnings about the negative consequences of premarital sex, observing changes during puberty, giving advice during pubertal changes, teaching genital hygiene practices, and raising children to act appropriate to their gender; 3) support for nurturing sexual growth, which includes having adequate knowledge about sexual health, comfort with family communication about sex, and raising children with love and warmth; and 4) constraints of raising a growing teenager, which includes being ashamed of talking about sex and lack of knowledge and skills about sexual health. The findings of this study provide essential knowledge about how to empower parents to have adequate knowledge and skills to nurture their growing teenagers with regards to SRH. This can contribute to the development of an intervention for parents to promote SRH among early adolescents.